E-commerce in business - Leigh, Richard; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2003)
This program provides three fascinating case studies, which is Ford, with their online marketing, Coronet (corporate uniform manufacture), with their online ordering system, and Mp3.com.au, with their online delivery of music
Title from title screen
Executive producer, Mark McAuliffe ; editor, Damien Bear ; graphics, reece Sanders ; camera, Marcus Dineen...[et al.]
Newsdesk: Eleaner Handley, Jim Pidgeon
Keywords: Electronic commerce -- Case studies; Internet -- Economic aspects; Internet marketing